1992
DOI: 10.1016/0266-7681(92)90126-m
|View full text |Cite
|
Sign up to set email alerts
|

Rupture of the Flexor Carpi Radialis Tendon Associated with Scapho-Trapezial Osteoarthritis

Abstract: A case of rupture of the flexor carpi radialis tendon in association with scapho-trapezial osteoarthritis is reported. The symptoms of pain and swelling contrast with the loss of function which characterizes rupture of other tendons in the hand and wrist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 13 publications
0
20
0
2
Order By: Relevance
“…The post-injection complication of tendon rupture is rare enough to be limited to case reports [2][3][4]. The etiology of FCR tendon rupture may also include tendon attrition from the scaphoid-trapezium-trapezoid (STT) joint [5]. Rupture of a digital flexor tendon leads to complaints related to loss of tendon function [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The post-injection complication of tendon rupture is rare enough to be limited to case reports [2][3][4]. The etiology of FCR tendon rupture may also include tendon attrition from the scaphoid-trapezium-trapezoid (STT) joint [5]. Rupture of a digital flexor tendon leads to complaints related to loss of tendon function [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Nontraumatic tendon or muscle ruptures occur occasionally, but most of them have an underlying pathology such as wrist arthritis or a history of local steroid injection. [1][2][3] Patients with rheumatoid arthritis are at high risk of tendon rupture because of repeated inflammation and steroid consumption. [14][15][16] This patient had no significant risk factors such as local steroid injection in the muscle or other systemic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Most reported flexor carpi radialis injuries are tendon ruptures associated with radius fracture, wrist arthritis, or a history of local steroid injection. [1][2][3][4] Acute muscle tears occur most commonly near the musculotendinous junction, followed by the epimysium area, and less commonly in the muscle belly. 5,6 We present an unusual case with a nontraumatic tear of the muscle belly of the flexor carpi radialis after regular swimming exercise.…”
mentioning
confidence: 99%
“…Examination may reveal a visible tendon defect, tenderness upon palpation and surgical exploration reveal fibrous neotendon or a gap visualised by radiological imaging. 8,9 Polatsch et al and Parellada et al (personal communication) has recently demonstrated tendon rupture on Magnetic Resonance Imaging (MRI). 14,15 The ruptured tendon may be easily visualised with inspection however in larger forearms normal anatomy may not be so clearly defined.…”
Section: Case Reportmentioning
confidence: 94%
“…We found only 15 cases reported in the literature. 1,2,5,7,9,[12][13][14][15][16][17] Isolated cases of FCR rupture are commonly associated with Scapho-Trapezium-Trapezoid (STT) osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%